Digital Transnational Dissidence and State Control: A Conceptual Reflection on the Practice and Limits of Digital Transnationalism - Hüsrev Tabak; Cenk Beyaz (Journal of Economy Culture and Society)
The historical practice of citizen participation in politics was confined to elections, yet in the digital era, increasing digitalisation in everyday life has opened windows of opportunities for alternative civilian participation in the political processes, oppositionary activities being foremost among them. Individual or collective opposition parties thus today also confidently carry out political activities against governmental politics through cyber and digital spaces, and thanks to digital advances, oppositionary political participation can no longer be confined to national borders. Hence, in forms of digital transnationalism and transnational dissidence, irrespective of the connection of the articulator to the target country, people around the world criticise governmental politics and shape public perceptions in one country from abroad. Nevertheless, governments, as well, make use of digital space in taking part in transnational practices in both shaping domestic and international public opinion and challenging overseas or domestic dissident digital transnationalism with an aim to increase its control over the narrative of its politics. This paper elaborates on this paradoxical relationship – the nexus of digital transnationalism, transnational opposition and state control. The paper examines how and why cyberspace turns into a domain for transnational political opposition and, in a related way, examines state endeavours to regulate and govern digital areas as a means of overseeing the digital transnationalism of (trans)local and transnational dissidence groups. Particularly with reference to the latter, the paper deliberates on the limits of digital transnationalism against state control.